Short term cardiovascular effects of aldosterone in healthy male volunteers - Schmidt, Bernhard; Montealegre Rodriguez, Carmen Alicia; Janson, C. P.; Martin, Nicole; Stein-Kemmesies, C.; Scherhag, Armin; Feuring, Martin; Christ, Michael; Wehling, Martin (The journal of clinical endocrinology & metabolism, 1999)
Clinical evidence of rapid, nongenomic aldosterone effects in the cardiovascular system has been provided by clinical studies; an increase in systemic vascular resistance (SVR) was shown by invasive techniques within 3 min after injection of aldosterone. Here, we study the dose dependency and the later course of the rapid aldosterone effects by noninvasive techniques.In 12 healthy male volunteers, SVR and heart rate variability were determined by impedance cardiography and digital electrocardiography, respectively, for 8 h after the injection of 0.05 or 0.5 mg aldosterone in a double blind, placebo-controlled, 3-fold cross-over study. No significant differences were observed for baseline values among the three treatments. The area under the curve of SVR during the first 45 min after injection was significantly different between the periods with the highest areas under the curve seen after the injection of 0.5 mg aldosterone (mean ± sd, 40.4 ± 12.8 vs. 36.8 ± 10.3 for 0.05 mg aldosterone and 36.8 ± 10.4 for placebo; P = 0.05). Individual comparisons showed significant differences at 6 and 30 min between placebo and the 0.5 mg aldosterone period (P < 0.05), with values for the 0.05 mg aldosterone period similar to those for the placebo period. From 330-390 min, opposite changes occurred; SVR was depressed during the 0.05 mg (P < 0.05) and 0.5 mg aldosterone periods compared with that during the placebo period. These delayed effects may reflect an increased vagal tone in the aldosterone groups, as demonstrated by higher values of the time domain parameter of heart rate variability pNN50.This study provides further evidence for clinically detectable rapid cardiovascular aldosterone effects in vivo obtained by noninvasive techniques. The data are consistent with the view of aldosterone as a rapid modulator of cardiovascular responses acting through nongenomic mechanisms.
Gesehen am 18.10.2022